2022
DOI: 10.3390/vaccines10030350
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Effectiveness of SARS-CoV-2 Vaccines: A Systematic Review and Meta-Analysis

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has threatened global health and prompted the need for mass vaccination. We aimed to assess the efficacy and effectiveness of COVID-19 vaccines to prevent mortality and reduce the risk of developing severe disease after the 1st and 2nd doses. From conception to 28 June 2021, we searched PubMed, Cochrane, EBSCO, Scopus, ProQuest, Web of Science, WHO-ICTRP, and Google Scholar. We included both observational and randomized controlled trials. The pooled vaccine effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 62 publications
2
35
0
Order By: Relevance
“…In addition to age, vaccine types, and the number of doses, most studies have suggested that country and duration since vaccination also affected the efficacy and immunogenicity of COVID-19 vaccines ( 40 , 41 , 96 98 ). Nevertheless, we did not detect significant correlations between continent and efficacy or immune effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age, vaccine types, and the number of doses, most studies have suggested that country and duration since vaccination also affected the efficacy and immunogenicity of COVID-19 vaccines ( 40 , 41 , 96 98 ). Nevertheless, we did not detect significant correlations between continent and efficacy or immune effects.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of mRNA-based vaccines in reducing infection incidence of COVID-19 after the second dose, irrespective of prior infection with SARS-CoV-2, is comparable (95%—Pfizer–BioNTech; 94.1%—Moderna). In turn, the clinical effectiveness of the analyzed adenovirus-vectored vaccine (Oxford–AstraZeneca) in the prevention of COVID-19 is 70.4% among subjects receiving the two recommended doses at any dosing intervals (between 3 and 23 weeks) [ 23 , 24 , 25 , 34 ]. Moreover, many performed studies have shown that a number of factors can influence the observed difference in efficacy and effectiveness of the COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…COV2.S [J&J/Janssen]), and inactivated vaccines (e.g., CoronaVac [Sinovac]) [12]. It is reported that the inactivated COVID-19 vaccines most widely used in China (e.g., BBIBP--CorV and CoronaVac) have a less effectiveness (66%-78%) [13,14] than the mRNA vaccines (BNT162b2 and mRNA-1273, >90%) used in Western countries [15,16]. Despite the proven effectiveness of COVID-19 vaccines in preventing severe COVID-19 outcomes, the global vaccination coverage remains far below expectations [17].…”
Section: Introductionmentioning
confidence: 99%